Systematic Review: Noise Exposure Risks and Factors Associated with Hypertension Incidence in Workers - Intan Sekar Arumdani; Onny Setiani; Tri Joko (Universitas Diponegoro, 2022)
Noise is associated with hypertension. Exposure to noise that exceeds quality standards can cause an increase in workers' blood pressure. This study was conducted to examine the risk of noise exposure and the factors associated with the incidence of hypertension in workers through a systematic review method. Article searches were conducted through the journal sites Google Scholar, Garuda Portal, Science Direct, Proquest, JSTOR, Scopus, Semantic Scholar, and PubMed. The selection of articles was carried out with the following criteria: the dependent and independent variables were the incidence of hypertension in workers and exposure to noise, open access full text, the articles selected were articles with a publication date of not more than 10 years (2012-2021), and articles in English. Indonesian and English. Based on 724 relevant articles, 9 main articles met the criteria and were discussed further in this study. 9 main articles showed statistical test results p-value <0.05 which means there is a significant relationship between noise exposure and the incidence of hypertension in workers. Other factors, namely age of workers, length of work, gender, use of ear protective equipment, BMI, and family history of hypertension all have a significant relationship with the incidence of hypertension.